A relation between two results about entire functions of exponential type - Koosis, P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
It is shown that the Beurling - Maliiavin multiplier theorem for the entire functions of exponential type can be derived from certain estimates for polynomials on the complex plane.